Decoding Gen Z talent attraction: How employer branding shapes media sector employment intentions - Iyer, Kavitha Venkatasubramany; K., Aryan; Al Hajj, Raghid; Saadouli, Nasreddine (Frontiers in Communication, 2026)
The influx of Gen Zs into the contemporary workforce and their differing perceptions and attitudes towards organizational values led this study to examine which employer values attract the best talent among younger individuals nearing the completion of their courses and actively seeking employment. Although Gen Z’s employer preference attributes and factors influencing their intent to join diverse industries have received considerable focus, the media sector has been curiously left out. Additionally, the media industry is experiencing a decline in employment opportunities, with a shortage of secure, well-paying jobs and fewer college placements. Hence, investigating which PBVs in media organizations attract Gen Zs became the study’s premise, carried out using the Employer Attractiveness (EmpAt) scale. Nineteen items relevant to the study’s aim were included in the survey instrument to collect responses from 312 media students from undergraduate colleges across India who had completed at least one industry internship and a project experience lasting 6 months. The multiple regression analysis revealed that, except for social value, the other four values significantly affect Gen Z’s PBV and employment intention within Indian media organisations. The results emphasize the importance of developing an employer branding strategy that focuses on attractiveness to attract culturally compatible Gen Z candidates to media organizations. The decoding outlines variation in employer attractiveness dimensions across cultural contexts (particularly in Asian and emerging economies) and generational backgrounds. The decoding also aims to show the effectiveness of the EmpAt scale, providing valuable insights for practitioners in the media sector and researchers.